A strong association of human leukocyte antigen-associated Pol and Gag mutations with clinical parameters in HIV-1 subtype A/E infection. - Tran, Giang Van; Chikata, Takayuki; Carlson, Jonathan M.; Murakoshi, Hayato; Nguyen, Dung Hoai; Tamura, Yoshiko; Akahoshi, Tomohiro; Kuse, Nozomi; Sakai, Keiko; Sakai, Sachiko; Cobarrubias, Kyle; Oka, Shinichi; et al. (AIDS, 2016)
Identification of human leukocyte antigen-associated HIV-1 polymorphisms (HLA-APs) in different global populations furthers our understanding of HIV-1 pathogenesis and may help identify candidate immunogens for HIV vaccines targeted to these populations. Although numerous population-based studies identifying HLA-APs have been conducted in HIV-1 subtype B- and subtype C-infected cohorts, few have focused on subtype A/E.We investigated HLA-APs in a cohort of chronically HIV-1 subtype A/E-infected Vietnamese individuals.HLA-APs in HIV-1 Gag, Pol, and Nef regions from 388 treatment-naive individuals chronically infected with HIV-1 subtype A/E were analyzed using phylogenetically informed approaches.A total of 303 HLA-APs were identified. HLA-APs occurring at six positions in Gag and six positions in Pol were significantly associated with higher plasma viral load (pVL), whereas HLA-APs occurring at two positions in Gag and 13 positions in Pol were significantly associated with lower CD4 T-cell counts. Furthermore, the proportion of Pol codons harboring an HLA-AP specific to the host's HLA correlated positively with HIV-1 pVL (R = 0.22; P < 0.0001) and inversely with CD4 T-cell counts (R = -0.32; P < 0.0001). Similarly, the proportion of HLA-associated Gag codons harboring host-specific HLA-AP correlated inversely with CD4 T-cell counts (R = -0.13; P = 0.01).These significant associations between HIV-1 amino acids adapted to Vietnamese HLA alleles and higher pVL and lower CD4 T-cell counts suggests that accumulation of cytotoxic T cells escape mutations may influence clinical outcomes in HIV-1 subtype A/E-infected Vietnamese individuals.